269 Societal participation of older people with and without a chronic disease: participation in paid work, volunteering and providing informal care. (24th April 2018) - Scharn, Micky; Beek, Allard J van der; Suanet, Bianca; Huisman, Martijn; Boot, Cécile RL
Abstract : Background: Societal participation in the Netherlands has increased due to policy changes. We do not know whether this increase in societal participation also counts for people with chronic disease. This study aims to explore differences and similarities in 3 forms of societal participation, having paid work, providing informal care and involvement in volunteer work, between people with and without a chronic disease in 2002 and 2012. Methods: Respondents (n=1, 779) aged between 55 and 64 years who participated in the representative Longitudinal Ageing Study Amsterdam in 2002 or 2012 were included. We tested differences in (combinations of) having paid work, providing informal care or volunteer work between participants with and without a chronic disease by regression analyses, taking into account sociodemographic confounders and effect modification by year (2002 vs 2012). Results: Having a chronic disease was associated with not having paid work (OR: 0.7; 95% CI: 0.6 to 0.9), but not with providing informal care (OR: 0.9; 95% CI: 0.7 to 1.2) or volunteer work (OR: 0.9; 95% CI: 0.7 to 1.1). No differences were found between workers with and without chronic disease for combinations of societal participation. We found effect modification by year; in 2012, people without (OR: 2.7; 95% CI: 1.7 to 4.5) and with chronic disease (OR: 3.0; 95% CI: 2.0 to 4.5) were more likely to have paid work compared to those without chronic disease in 2002. Conclusion: The present study showed that people with a chronic disease aged 55–64 years were less likely to be involved in paid work, but we did not find indications for differences in participation in providing informal care or volunteer work. However, we did find a time effect for participation in paid work for people with and without a chronic disease in 2012 compared to 2002. Future research should focus on differences in social participation within the heterogeneous group with chronic disease, as differences may be present in subgroups.